2000
DOI: 10.1046/j.1469-8137.2000.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids accumulate in leaves and glandular trichomes of Phillyrea latifolia exposed to excess solar radiation

Abstract: Experiments were conducted on Phillyrea latifolia plants grown under a dense overstorey of Pinus pinea (shade plants) or on seashore dunes (sun plants) in a coastal area of Tuscany (42m 46h N, 10m 53h E). Total integrated photon flux densities averaged 1n67 and 61n4 m mol m −# d −" for shade and sun sites, respectively. A leaf morphological-structural analysis, a qualitative and quantitative analysis of phenylpropanoids of leaf tissue and leaf surface, and a histochemical localization of flavonoids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 57 publications
11
175
0
10
Order By: Relevance
“…Although the central pathway for flavonoid biosynthesis is conserved in plants, various enzymes such as isomerases, reductases, hydroxylases, methyltransferases, glycosyltransferases, and acyltransferases are known to modify the basic flavonoid skeleton, leading to the species-specific flavonoids. Flavonoid glycosides were found exclusively in the secretory products of glandular trichomes of Phillyrea latifolia leaves when exposed to high levels of sunlight, which suggested the flavonoids in glandular trichomes probably provide UV-protection for plants (Agati and Tattini 2010;Tattini et al 2000).…”
Section: Phenylpropanoids and Polyketidesmentioning
confidence: 98%
“…Although the central pathway for flavonoid biosynthesis is conserved in plants, various enzymes such as isomerases, reductases, hydroxylases, methyltransferases, glycosyltransferases, and acyltransferases are known to modify the basic flavonoid skeleton, leading to the species-specific flavonoids. Flavonoid glycosides were found exclusively in the secretory products of glandular trichomes of Phillyrea latifolia leaves when exposed to high levels of sunlight, which suggested the flavonoids in glandular trichomes probably provide UV-protection for plants (Agati and Tattini 2010;Tattini et al 2000).…”
Section: Phenylpropanoids and Polyketidesmentioning
confidence: 98%
“…Several studies have demonstrated the change in flavonoid composition of plant leaves as a consequence of excess light or UV-radiation (Lois 1994, Olsson et al 1998, Hofmann et al 2000, Tattini et al 2000, Kolb et al 2001. The activation of flavonoid biosynthetic genes by UV-radiation has been shown in a number of studies (Logemann et al 2000).…”
Section: Environmental Significance Of Flavonoids In Plantsmentioning
confidence: 99%
“…However, in light of the significantly higher total number in the leaves after DWGW treatment, it is probable that DWGW treatment induced an increase in glandular trichomes in silver birch seedlings and an increase in non-glandular trichomes in pubescent birch seedlings. It has been suggested that both types of trichomes are involved in protection against water loss by reducing air movement at the leaf surface and by increasing the thickness of the boundary layer of leaves (Tattini et al 2000). Moreover, both types of trichomes were mainly on the veins (II, Figure 1b, c) so they can also be physically bound to the water movement between the inner and outer parts of the leaves as suggested by Fernández et al (2014).…”
Section: Leaf and Stem Morphologymentioning
confidence: 96%